Impact of rock mineralogy on reactive transport of CO2 during carbon sequestration in a saline aquifer - Mohamed Gamal Rezk; Ahmed Farid Ibrahim (Journal of Petroleum Exploration and Production Technology)
Abstract Deep saline aquifers offer a vast long-term storage capacity for CO2. The diverse mineral compositions in CO2 geological storage systems complicate the reactive transport of CO2. Despite extensive research on carbon sequestration in saline aquifers, the impact of rock mineralogy on the CO2 trapping mechanisms needs further investigation. This study addresses this gap by employing numerical simulations to investigate how different minerals affect the reactive transport of CO2 during injection into saline aquifers. A compositional simulation model was created, wherein CO2 is injected for 25 years, followed by a 3000-year shut-in period. Various parameters, including CO2 plume migration, changes in pH, water density variations, mineral dissolution and precipitation, and porosity changes in the reservoir rock, are examined to understand the complex CO2–brine–rock interactions. The effect of formation mineralogy on CO2 trapping mechanisms was investigated. To do so, a sensitivity study was conducted and then, special cases with extreme mineral concentrations were studied. The simulation results highlight the profound effects of different minerals on the CO2 trapping mechanisms. Quartz exhibits minimal dissolution, while calcite plays a crucial role, initially dissolving due to low pH and later precipitating after around 300 years. Anorthite dissolution provides ions for kaolinite precipitation, and the release of calcium ions from anorthite dissolution contributes to carbonate minerals precipitation. Porosity changes in the reservoir rock are observed, with regions experiencing an increase due to early calcite dissolution and subsequent changes associated with mineral precipitation. Sensitivity analysis showed that Anorthite and Illite facilitate more CO2 mineralization, with Anorthite and Illite showing 0.68 and 0.46 correlation with mineral trapping, respectively. Conversely, minerals like Calcite and Kaolinite positively correlated with CO2 solubility, with correlations of + 0.21 and + 0.23 respectively, without significantly promoting its conversion into mineral forms, while Quartz, K-Feldspar, and Dolomite show minor effects on CO2 trapping mechanisms. Elevating Anorthite concentrations speeds up CO2 mineralization, ensuring secure storage in saline aquifers, with a minimum threshold concentration of 0.05 volume fraction; beyond this point, no further changes in CO2 mineralization are observed. Formation brine salinity significantly affects CO2 solubility and, consequently, mineral trapping, as higher salinity levels hinder CO2 dissolution and restrict its availability for geochemical reactions with rock minerals. This study offers insights that can inform reservoir characterization and management practices, ultimately enhancing the effectiveness of carbon sequestration efforts.